Efektivitas Terapi Mindfulness Berbasis Aplikasi Breathe2Relax Terhadap Stres Mahasiswa Tingkat Akhir - Mira Agusthia; Utari Christya Wardhani; Novita Rochmayanti; Triyana Harlia Putri (Malahayati Nursing Journal, 2024)
ABSTRACT Academic stress is defined as a condition of individuals experiencing pressure from the perception and assessment of academic stressors, which are related to science and education in higher education. The prevalence of students in the world who experience stress is 38-71%. Meanwhile, the prevalence of students experiencing stress in Indonesia was 36.7-71.6%. Stress cannot be prevented but it can be managed. Non-pharmacological therapy for stress reduction is application-based mindfulness. The “Breathe2Relax” app is also a portable skill training tool for practicing diaphragmatic breathing. Mindfulness brings students to focus on realizing the conditions they are currently facing, accepting them with sincerity, without reacting and giving judgments. To determine the effectiveness of Mindfulness Therapy based on the Breathe2Relax Application on Final Year Student Stress. Quantitative research quasi-experimental one group pretest - posttest design without a control group and sampling using purposive sampling with a total sample of 34 students. The level of stress before being given mindfulness therapy was moderate stress as many as 32 people (94.1%) and severe stress as many as 2 people (5.9%). The stress level of students after being given mindfulness therapy was 29 people (85.3%) mild stress and 5 people (14.7%) moderate stress. The results of the analysis test showed that there was an effectiveness of mindfulness therapy based on the Breathe2Relax application on stress in final year students at Awal Bros University. p value=0.000 (p0.05). There is an effect of the effectiveness of mindfulness therapy based on the "Breathe2Relax" application on stress in final year students. It is hoped that the research place will conduct counseling guidance as a place of guidance for students so that it can reduce the level of stress that occurs in students. Keywords: Student, Stress, Mindfulness Therapy  ABSTRAK Stress akademik diartikan sebagai suatu keadaan individu yang mengalami tekanan hasil persepsi dan penilaian tentang stressor akademik, yang berhubungan dengan ilmu pengetahuan dan pendidikan di perguruan tinggi. Prevalensi mahasiswa di dunia yang mengalami stres didapatkan sebesar 38-71%. Sementara itu prevalensi mahasiswa yang mengalami stres di Indonesia sendiri didapatkan sebesar 36,7- 71,6%. Stres tidak dapat dicegah tetapi bisa dikelola. Terapi non farmakologi penurunan stres yaitu mindfulness berbasis aplikasi. Aplikasi “Breathe2Relax” juga merupakan alat latihan keterampilan portabel untuk melatih pernapasan diafgrama. Mindfulness membawa mahasiswa untuk fokus menyadari kondisi yang dihadapi saat ini, menerimanya dengan penuh keikhlasan, tanpa bereaksi dan memberikan penilaian. Tujuan untuk mengetahui Efektivitas Terapi Mindfulness berbasis Aplikasi Breathe2Relax terhadap Stres Mahasiswa Tingkat Akhir. Penelitian kuantitatif quasi experimental one grup pre test - post test design tanpa kelompok kontrol dan pengambilan sample menggunakan Purposive Sampling dengan jumlah sample sebanyak 34 mahasiswa. Tingkat stres sebelum diberikan terapi mindfulness stres sedang sebanyak 32 orang (94,1%) dan stres berat sebanyak 2 orang (5,9%). Tingkat stres mahasiswa setelah diberikan terapi mindfulness yaitu stres ringan sebanyak 29 orang (85,3%) dan stres sedang sebanyak 5 orang (14,7%). Hasil uji analisis didapatkan bahwa terdapat efektivitas terapi mindfulness berbasis aplikasi Breathe2Relax terhadap stres pada mahasiswa tingkat akhir Universitas Awal Bros. p value=0,000 (p0,05). Ada pengaruh efektivitas terapi mindfulness berbasis aplikasi “Breathe2Relax” terhadap stres pada mahasiswa tingkat akhir. Diharapkan  tempat penelitian melakukan bimbingan konseling sebagai tempat bimbingan bagi mahasiswa sehingga dapat mengurangi tingkat stres yang terjadi pada mahasiswa. Kata Kunci: Mahasiswa, Stres, Terapi Mindfulness